1993
DOI: 10.1128/mcb.13.7.4011
|View full text |Cite
|
Sign up to set email alerts
|

DNA-binding specificities of the GATA transcription factor family.

Abstract: Members of the GATA family of transcription factors, which are related by a high degree of amino acid sequence identity within their zinc finger DNA-binding domains, each show distinct but overlapping patterns of tissue-restricted expression. Although GATA-1, -2, and -3 have been shown to recognize a consensus sequence derived from regulatory elements in erythroid cell-specific genes, WGATAR (in which W indicates A/T and R indicates A/G), the potential for more subtle differences in the binding preferences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
374
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(387 citation statements)
references
References 41 publications
11
374
2
Order By: Relevance
“…The first of these sites, termed CEF-1, contains the nucleotide sequence AGATIA, which conforms to one of the high-affinity GATA-binding sites identified by random site selection analyses but differs from the consensus GATA-binding sequence (WGATAR) by a single nucleotide substitution (Fig. 1A) (32,42,51). In addition, the second nuclear protein-binding site in the cTnC enhancer, CEF-2, contains the nucleotide sequence GGATAT, which contains the GATA core motif but differs from the consensus GATA-binding sequence in its flanking residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of these sites, termed CEF-1, contains the nucleotide sequence AGATIA, which conforms to one of the high-affinity GATA-binding sites identified by random site selection analyses but differs from the consensus GATA-binding sequence (WGATAR) by a single nucleotide substitution (Fig. 1A) (32,42,51). In addition, the second nuclear protein-binding site in the cTnC enhancer, CEF-2, contains the nucleotide sequence GGATAT, which contains the GATA core motif but differs from the consensus GATA-binding sequence in its flanking residues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, basic helix-loop-helix myogenic transcription factors are not expressed in developing heart or precardiac mesoderm (49,63,64), and mice contain-Previous studies have demonstrated that the known GATA transcription factors bind the consensus motif (A/ T)GATA(A/G) (16,73). Random site selection has suggested that additional nonconsensus sequences can bind GATA proteins with high affinity (32,42). Two of the GATA transcription factors (GATA-1 and GATA-3) are expressed in a tissuerestricted fashion and have been shown previously to regulate lineage-specific gene expression in erythroid cells and T lymphocytes, respectively (24,29,33,72,78).…”
mentioning
confidence: 99%
“…GATA1 binds DNA directly via subdomains of its 2 zinc fingers, most importantly the C-finger (52,53). However, several disease-associated amino acid substitutions within the N-finger inhibit GATA1 binding to target genes in vivo, yet have no effect on in vitro binding to naked DNA templates.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-cGATA-2 monoclonal antibody was prepared using bacterially expressed GST/cGATA-2 fusion protein (Ko & Engel 1993). Briefly, Ϸ 100 mg of GST/cGATA-2 was injected into mice using Titremax adjuvant.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%